METHOD OF PERDICTING THE SUCCESS OF THE IMLPEMENTATION OF SCIENTIFIC ITPROJECTS BASED ON THE ANALYSIS OF THEIR CHARACTERISTICS (Computer systems and information technologies, 2020)
The paper further developed the method of predicting the success of the implementation of scientific IT projects based on the analysis of their characteristics. The paper argues for the need to deepen the analysis of requirements, the dependence of the success of the scientific IT project on the requirements, the relevance and importance of the ability to assess the possible success of the project based on requirements, and the need to support the developer and the customer, which now are guided in making such a choice only by the cost and duration of the project, as well as their own intuition. The developed method consists of: neural network prediction of project characteristics based on requirements analysis; interpretation of the obtained relative values of the project characteristics on the basis of the integrative project indicator; assessing the degree of success of project implementation on the basis of an integrative project indicator; predicting the category of success of scientific IT project (successful, challenged, failed) based on the degree of success of the project implementation. The input data for the developed method of predicting the success of the implementation of scientific IT projects based on the analysis of their characteristics is a set of indicators form the requirements, and the result of the method is a conclusion on the category of success of project implementation, which allows making an informed choice of the project for further implementation. The developed method differs from the known ones in that it allows to predict the success of project implementation, to compare projects comprehensively according to the main characteristics and the predicted success of project implementation (and not only by cost and duration, as it happens now) and to make a reasonable choice of project for further implementation.
Keywords: scientific IT project; project characteristics; method of predicting the success of the implementation of scientific IT projects; the degree of success of the project implementation; the category of project success